2020
DOI: 10.1073/pnas.1916553117
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism indicates that primary magnetite in zircon records a strong Hadean geodynamo

Abstract: Determining the age of the geomagnetic field is of paramount importance for understanding the evolution of the planet because the field shields the atmosphere from erosion by the solar wind. The absence or presence of the geomagnetic field also provides a unique gauge of early core conditions. Evidence for a geomagnetic field 4.2 billion-year (Gy) old, just a few hundred million years after the lunar-forming giant impact, has come from paleomagnetic analyses of zircons of the Jack Hills (Western Australia). He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 57 publications
4
64
1
Order By: Relevance
“…The presence of a CRM means that the thermal paleointensity experiments, which implicitly assume that the NRM is a TRM, will yield unreliable paleointensity values. We also note that unlike the previous studies (7,8), we found that the majority of grains analyzed paleomagnetically have poor demagnetization and remagnetization behavior. In conclusion, the existence of the dynamo before 3.5 Ga has yet to be established.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The presence of a CRM means that the thermal paleointensity experiments, which implicitly assume that the NRM is a TRM, will yield unreliable paleointensity values. We also note that unlike the previous studies (7,8), we found that the majority of grains analyzed paleomagnetically have poor demagnetization and remagnetization behavior. In conclusion, the existence of the dynamo before 3.5 Ga has yet to be established.…”
Section: Discussioncontrasting
confidence: 98%
“…The alignment, aspect ratios, and locations of the magnetite grains within regions of recovery from accumulated radiation damage demonstrate that the grains are secondary in origin (20)(21)(22). No evidence has been put forth to support the speculation that they formed by exsolution and/or vapor deposition (8). The presence of secondary magnetite is not linked to alteration during laboratory heating steps, as demonstrated by the fact that these two grains passed paleomagnetic criterion (a) and that they contain voids with a diversity of shapes and sizes that commonly are empty or filled with phases other than magnetite, most commonly baddeleyite and ilmenite (23).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on measurements on selected quartz crystals from the Greenstone Belt of the Kaapvaal craton of South Africa, it has been inferred that a magnetic field half as strong as today's existed 3.2 billion years ago and a field of strength about 70% of the present existed 3.45 billion years ago (Tarduno et al 2010). More recently, analyses of zircons from the Jack Hills (Western Australia) provide evidence for a geomagnetic field 4.2 billion year old, just a few hundred million years after the lunar-forming giant impact (Tarduno et al 2020), although other scientists still debate this issue.…”
Section: Resulting Knowledgementioning
confidence: 99%
“…There are multiple Earth analogues in the Solar System (and more beyond) that could provide insights into Earth's history and future. Even when planetary bodies are not analogous to Earth, they span a range of sizes, environments and compositions that allow us to approach comparative planetology as a grand, full-scale experiment to systematically develop quantitative models of geological and atmospheric processes that pertain to our understanding to Palaeoarchaean eons are ambiguous 25,26 , solving the new core paradox may require that we turn towards other worlds.…”
Section: Core and Dynamo Formationmentioning
confidence: 99%